5-6 gadīgo bērnu radošās domāšanas attīstība āra nodarbībās - Peipe, Kintija (Latvijas Universitāte, 2024)
Kvalifikācijas darbs “5-6 gadīgo bērnu radošās domāšanas attīstība āra nodarbībās”: izstrādāts ar mērķi teorētiski pētīt un empīriski pamatot 5-6 gadīgo bērnu radošās domāšanas attīstību āra nodarbībās. Pētījuma objekts: āra nodarbības Pētījuma priekšmets: 5-6 gadīgo bērnu radošās domāšanas attīstība Pētījuma mērķis: teorētiski pētīt un empīriski pamatot 5-6 gadīgo bēru radošās domāšanas attīstību āra nodarbībās. Pētījuma jautājums: “Kā āra nodarbības ietekmē 5-6 gadīgo bērna radošo domāšanu? Uzdevumi: 1.Analizēt teorētisko literatūru par radošās domāšanas attīstību 5-6 gadīgiem bērniem. 2.Veikt teorētiskās literatūras analīzi par radošuma veicināšanu āra nodarbībās. 3.Veikt empīrisku pētījumu par radošās domāšanas sekmēšanu āra nodarbībās 4.Analizēt pētījuma rezultātus, veikt secinājumus par radošuma veicināšanu āra nodarbībās. Metodes: 1.Teorētiskās, zinātniskās un metodiskās literatūras analīze. 2.Empīriskās, pedagoģiskā novērošana, pedagoģiskā plāna izstrāde. Pētījuma bāze: Valmieras pirmsskolas izglītības iestāde X, 10 bērni (5-6 gadi). Darba struktūra: teksts atspoguļots uz 35 lpp., kas sadalīts anotācijā latviešu un angļu valodā, ievadā, 3 nodaļas, nobeigumā, secinājumos, literatūras un avotu sarakstā un pielikumā. Pētījumā ilustrēti 3 attēli, 7 tabulas. Atslēgas vārdi: radošā domāšana, āra nodarbības, kreativitāte, dabas materiāli, pirmsskolas trešais posms 5-6 gadi.

Qualifications work “Development of creative thinking of 5-6 caring children in outdoor lessons.”: Developed with the aim of theoretically researching and empirically substantiating development of creative thinking of 5–6-year-old children in outdoor lessons. Object pf study: outdoor lessons. Subject of the research: development of creative thinking of 5–6-year-old children. Point of the research: to theoretically study empirically substantiate the development of 5–6-year-olds in outdoor lessons. Research question: “How do outdoor lessons affect the creative thinking of 5–6-year-old children”. Tasks: 1.Analyze the theatrical literature about the creative thinking of 5–6-year-old children. 2.To conduct analysis of the theoretical literature on the promotion of creativity in outdoor lessons. 3.To conduct an empirical study on the promotion of creative thinking in outdoor classes. 4.Analyze the results of the study, draw conclusions about the promotion of creativity in outdoor classes. Methods: 1.Analysis of theoretical, scientific, and methodological literature. 2.Empirical, pedagogical observation, development of a pedagogical plan. Research base: Valmiera preschool education institute X, 10 children (5–6-year-old). Key words: creative thinking, outdoor activities, creativity, materials for nature, the third stage of kindergarten 5–6-year-olds. Scientific categories: after exposure to the object – experimental; data processing – quantitative; for usability – fundamental; data collection procedures – observation; type of research question – descriptive studies, activities. Work structure: text is mirrored on 36 pages, which is divided in an annotation in Latvian and English, introduction, 3 departments, at the end, conclusions, in the list of literature sources and the appendix. Illustrated un the study are three photos and 7 charts, 30 literature courses.
Development of creative thinking of 5-6 caring children in outdoor lessons
Keywords: Izglītības zinātnes; Radošā domāšana; Āra nodarbības; Kreativitāte; Dabas materiāli; Pirmsskolas trešais posms 5-6 gadi